Risk Mitigation and Hazard Analysis in the Battery Production Process Using the Fuzzy Fault Tree Analysis Method - Ariffa, Anggelia; Tranggono, Tranggono; Sari, Rizqi Novita (Newinera Publisher, 2025)
Industrial Revolution 4.0 increases the demand for batteries but also increases the risk of workplace accidents in factories such as PT TMB. Production processes involving chemicals and heavy equipment cause potential hazards. In the last three years, accidents have increased, disrupting production and adding costs. Therefore, this research aims to identify risks and provide risk mitigation in the battery production process. This research uses Fuzzy Fault Tree Analysis (FFTA) to identify hazards and reduce risks, in order to improve the safety and competitiveness of the company. This research was conducted at PT TMB by combining qualitative analysis to understand general conditions and quantitative to analyze the risk of workplace accidents, such as fire, fatigue, operator injury, and worker health. The Fuzzy Fault Tree Analysis (FFTA) method was used to map and reduce potential hazards, as well as develop more effective work safety policies. The results of the research explained that there are four top events with different probabilities and impacts: fire risk (A) 26.82%, occupational fatigue (B) 11.57%, occupational injury (C) 40.58%, and occupational health (D) 21.03%. From the four top events mentioned above, mitigation is focused on the 3 highest positions based on the assessment of the matrix table, which are fire risk, occupational injury, and occupational health.